The Impact of Agile Methodology on Software Team’s Work-Related Well-Being - Omar, Mazni; Syed Abdullah, Sharifah Lailee (SERSC, 2015)
Agile methodology is people-oriented.However, little evidence demonstrates the methodology effectiveness on humanistic aspects.Work-related well-being is measured to what extent the agile methodology can give impact on anxiety, contentment, depression, and enthusiasm level among software engineering (SE) teams.This paper aims to investigate empirically the effect of agile methodology on software development team’s work-related well-being.To achieve this goal, a comparison study was carried out in an academic setting. A quantitative approach using statistical analysis was used to investigate the effect. Results showed that agile does not significantly affect work-related well-being.Nonetheless, the team that is able to apply the agile practices as closely as possible experienced higher level of enthusiasm during software project.This study provides additional empirical data in software engineering research and practices specifically on human aspects.Further investigation needs to be carried out on the software projects with higher task complexity.